THE STUDY OF POPULATION SATISFACTION WITH THE STATE OF THE MARKETS OF PRESCHOOL EDUCATION, ADDITIONAL EDUCATION OF CHILDREN - Bolshakova, Yulia; Bolshakov, Sergey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article discusses the problems of implementing state policy in the field of school education and preschool sphere. The article analyzes the results of a sociological study on the example of the educational services market Leningrad region. The results of a sociological study allow us to identify certain shortcomings in the organization of public services at the municipal level of government. The article discusses such aspects of organizing a competitive environment in the field of education as the number of organizations in the market, the representation of organizations in the market, the quality of services, price and the choice of organization. The results of the study allow us to note that more than a third of respondents are satisfied with the quality of services, and the choice of organization, and pricing policy. At the same time, the majority of respondents express certain doubts about these indicators, which is expressed in a small amount of differences between negative and positive values. The results of the study allow us to state the relevance of research on the quality of the organization of the provision of services in the field of preschool education, additional education of children, the market of psychological and pedagogical support services for children with disabilities. Studies show the high importance that households in the Leningrad Region attach to the education sector. This study allows us to identify areas of managerial impact to local authorities regulating these services.Monitoring the state of the market for services in the field of school and preschool education makes it possible to identify problem organizations and directions for solving social and economic problems in the field of educational organization. The education sector for all modern states is an important political component, the accessibility and universality of education is a constitutional indicator of the status - “social”, “rule of law”.